Strengthening national public health institutes: a systematic review on institution building in the public sector - Brugnara Kirchmann, Lúcia; Jaramillo, Catalina; Olarte-Peña, Margarita; Karl, Larissa; Deckert, Andreas; Marx, Michael; Horstick, Olaf; Dambach, Peter; Fehr, Angela (Frontiers in Public Health, 2023)
IntroductionStrong and efficient institutions are vital to the development of well-functioning governments and strong societies. The term “institution building” encompasses the creation, support, development, and strengthening of organizations and institutions. Still, there is little aggregated evidence on “institution building” considering a wider system-thinking approach, best practices, or development cooperation specifically in the field of public health. In 2007, the International Association of National Public Health Institutes (IANPHI) created a guiding Framework that countries may use for developing National Public Health Institutes (NPHIs). This Framework is currently being revised.MethodsIn this context, we conducted a systematic review to facilitate this revision with recent evidence on institution building and its potential contribution to NPHI. We followed the PRISMA guidelines for systematic reviews, searching for relevant publications in seven scientific databases (Pubmed, VHL/LILACS, EconLit, Google Scholar, Web of Science, World Affairs Online, ECONBIZ) and four libraries (World Bank; European Health for All database of the World Health Organization European Region, WHO; Organization for Economic Cooperation and Development, OECD; and the African Union Common Repository). The search was carried out in October 2021. We used the “framework analysis” tool for systematically processing documents according to key themes.ResultsAs a result, we identified 3,015 records, of which we included 62 documents in the final review. This systematic review fills a major gap of aggregated information on institution building in the field of public health and National Public Health Institutes. It is to our knowledge the first systematic review of this kind. The overriding result is the identification and definition of six domains of institution building in the health sector: “governance,” “knowledge and innovation,” “inter-institutional cooperation,” “monitoring and control,” “participation,” and “sustainability and context-specific adaptability.”DiscussionOur results show that the described domains are highly relevant to the public health sector, and that managers and the scientific community recognize their importance. Still, they are often not applied consistently when creating or developing NPHIs. We conclude that organizations engaged in institution building of NPHIs, including IANPHI, may greatly benefit from state-of-the-art research on institution building as presented in this study.
Gesehen am 14.07.2023